SCHOOL RESILIENCE ECOSYSTEM: MODEL KONTRA-RADIKALISME BERBASIS TRADISI PESANTREN MENGHADAPI CYBER-RADICALISM DI KALANGAN GEN-Z - Hadi Santoso; Ahmad Mukhlasin; Muslikhun Ibrohim Hizbulloh (Universitas Nahdlatul Ulama Surakarta, 2026)
In 2024, the escalation of radicalism into the digital sphere, known as cyber-radicalism, poses a critical threat to Generation Z by exploiting social media algorithms to propagate exclusive ideologies. Amidst this digital vulnerability, pesantren-based madrasahs in Solo Raya demonstrate unique resilience mechanisms grounded in local wisdom. This study aims to analyze the construction of school resilience in countering radical narratives across three strategic institutions: MA Al-Muayyad Surakarta, MA Al-Manshur Klaten, and MA Al-Muttaqien Pancasila Sakti. Employing a qualitative method with a multi-site case study design, the research draws upon data from in-depth interviews, observations, and documentation. The findings reveal a comprehensive